Directory of Manuscripts as Objects of Cultural Promotion in Petang and Abiansemal Sub-Districts, Badung Regency - I Gusti Agung Paramita; W.A. Sindhu Gitananda; I Nyoman Adi Wiratma; I Made Bram Sarjana; Ida Ayu Putu Santhi Stiti (International Journal of Interreligious and Intercultural Studies, 2025)
Badung Regency as the tourism center of Bali is interested in promoting culture, including making culture a paradigm of regional development. Efforts to make culture a paradigm of development by the spirit of cultural promotion must be initiated by identifying and mapping the objects of cultural promotion owned by Badung Regency and preparing a directory of cultural promotion targets in Badung Regency. One of the objects targeted for research here is manuscripts. This research was conducted in two sub-districts in Badung Regency, Petang and Abiansemal. This research used qualitative research methods. Data was collected using observation techniques, semi-structured interviews, and document studies. The determination of informants was done purposively. The selected informants are those considered to know information related to the object of cultural promotion. In this research, the data analysis technique used is descriptive-qualitative analysis. The data analysis stage in qualitative research generally starts with data collection, reduction, presentation, and conclusion drawing or verification. Based on the results of data analysis, the following picture was obtained: in the Petang sub-district, 10 locations of manuscripts were identified and mapped in the form of lontar, inscriptions, and Purana, while in the Abiansemal sub-district, 32 locations of manuscripts consisting of lontar, inscriptions, and Purana were identified and mapped. In total, there are 42 manuscript locations in Petang and Abiansemal.